The professional stress of nurses employed in medical institutions in the Lublin Region - Michalik, Joanna; Zawadka, Magdalena; Wolski, Dariusz; Stanisławek, Andrzej; Węgorowski, Paweł (Journal of Education, Health and Sport, 2017)
Introduction: Nursing, as a profession related to the protection and salvation of life, appears as particularly difficult, complex and multi-tasking. There are a number of specific burdens on the specifics of the problem, which include, first of all, the occurrence of unpredictable situations that endanger the health and well-being of patients. All this makes the profession of nurse a particularly stressful job. Research shows that as a result of occupational stress, many nurses complain about health problems and disorders in the physical, psychological, emotional and social spheres. A large group of nurses also work in the workplace experiencing symptoms of burnout syndrome Purpose of the work: The main research problem of work is about the sources of stress that are taking place in the work of investigated nurses and how the respondents deal with stress. Material and Methodology: The study was conducted in 2015. They covered 150 nurses employed in hospitals and health clinics located in the Lubelskie voivodeship. A modified scale is used to determine the sources of stress for nurses: Situation at the workplace M. Frese, which enables diagnosis of four primary sources of occupational stress, ie: work related; Physical environment; Social environment and other stressors. Results: The results show that the most stressful factors in the work of nurses are: too much work, too much time pressure during tasks, Conflicts with superiors, too low pay and lack of development opportunities. Conclusions: Nurses were heavily exposed to psychological stressors affecting their work. Most of the nurses surveyed were satisfied with their work, but a significant percentage of the respondents reported symptoms of chronic stress and fatigue.